Development of Multi Item Probabilistic Inventory Model by Considering Perishable and Purchase Bonus Factors - Limanjaya, Billy; Silitonga, Roland Y. H. (Yayasan Petra Harapan Bangsa, 2018)
Probabilistic inventory model is used mostly in a condition when the demand has uncertainty but the pattern can be predicted, which is the most applicable model in real situation. There are two models considered in the study as the base. In the first previous model, purchase bonus policy was applied to probabilistic inventory model, considering purchase bonus that was given by the supplier. Other model was built considering perishable factor that affect inventory cost based on deterministic demand condition. The purpose of this research is to combine those models, a probabilistic inventory model considering perishable and purchase bonus factors. The model was built for multi item with single supplier case. By comparing the models, it can be concluded that the developed model was comprehensive and applicable in real condition.